Short Tandem Repeat Variation in the CNR1 Gene Associated With Analgesic Requirements of Opioids in Postoperative Pain Management - Kasai, Shinya; Nishizawa, Daisuke; Hasegawa, Junko; Fukuda, Ken-ichi; Ichinohe, Tatsuya; Nagashima, Makoto; Hayashida, Masakazu; Ikeda, Kazutaka (Frontiers in Genetics, 2022)
Short tandem repeats (STRs) and variable number of tandem repeats (VNTRs) that have been identified at approximately 0.7 and 0.5 million loci in the human genome, respectively, are highly multi-allelic variations rather than single-nucleotide polymorphisms. The number of repeats of more than a few thousand STRs was associated with the expression of nearby genes, indicating that STRs are influential genetic variations in human traits. Analgesics act on the central nervous system via their intrinsic receptors to produce analgesic effects. In the present study, we focused on STRs and VNTRs in genes that encode receptors or neuropeptides and are associated with individual differences in postoperative pain management. All four STRs and VNTRs in the CNR1, GRIN2A, PENK, and PDYN genes were not associated with peripheral pain sensation. Short tandem repeats in the CNR1, GRIN2A, and PENK genes were associated with analgesic requirements after open abdominal surgery and orthognathic cosmetic surgery, and the association between STRs in the CNR1 gene and analgesic requirements after orthognathic cosmetic surgery was confirmed by Holm’s multiple-testing correction. These findings indicate that STRs in the CNR1 gene influence analgesia in the orofacial region.